Davids Against Goliath? Collective Identities and the Market Success of Peripheral Organizations During Resource Partitioning - Liu, Min; Wezel, Filippo Carlo (Organization Science, 2015)
This paper contributes to the sociology of markets literature by arguing that collective identities sustain the market success of peripheral producers during the process of resource partitioning. Two conditions underlie the positive returns obtained by peripheral producers from their identity claims. First, the demise of near-center producers crystallizes the difference among classes of organizations which benefits the market success of peripheral producers. Second, individual peripheral producers (i) facing an audience that values their identity claims and (ii) exhibiting credible engagement with their claimed identity encounter greater market success. Our contributions to the literature are discussed.